Eksistensi Desa Muslim Kampung Kusamba tahun 1990 - 2015 - Aditama, Yudha; Wirawan, A.A Bagus; Wahyuni, A.A Rai (Humanis, 2022)
This study aims to examine the existence of the Muslim Community in Kusamba Village. Their existence had a significant role in the Gelgel Kingdom, Klungkung Kingdom and other Balinese Kingdoms until they were given land around the Kusamba beach to take care of their Muslim community. The people of Kampung Kusamba who had helped in the war against colonialism in Klungkung earned them respect as Nyama Slam (Distant Brothers). The results of this study are how the existence of the Kusamba Village community can survive and maintain its existence due to the social interaction skills of the Kusamba Muslim community in social relations with the Balinese people so that it can be accepted. Using the existence theory of Jean Paul Sarte and the methodology of social history, this helps the author to reveal the life of the people of Kampung Kusamba with their own culture and blend with Balinese culture in Klungkung Regency.